Lightning-induced surge in transmission towers calculated using full-wave electromagnetic analysis and the method of moments - Anderson De Araujo, R. J. [UNESP]; Kurokawa, Sergio [UNESP]; Seixas, Claudiner Mendes De; Kordi, Behzad (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Lightning-induced surges can cause backflashovers in transmission lines which lead to outages in power systems. In this context, the tower-footing grounding impedance and tower surge impedance play fundamental roles in reducing the lightning-induced surges. The tower footing grounding impedance and tower surge impedance have been evaluated by many models and numerical methods in the frequency and the time domain. The tower-footing grounding system is represented by lumped or distributed parameter models and the tower surge impedance is calculated by geometric solid models or lumped circuits. In this article, the full-wave solution of Maxwell's equations using the method of moments is used for calculating the tower-footing grounding impedance of counterpoise electrodes in the frequency domain for various values of soil resistivity. Then, the admittance of two different transmission towers is calculated for various soils by the same method. Once the admittance of the combined tower and the footing is obtained, a lumped circuit model is developed that will enable the lightning-induced surge calculation directly in time domain.
Keywords: Backflashover; Electromagnetic transients; Grounding electrodes; Transmission towers